Timely relaparotomy after caesarean section of a moribund patient can save the life (Journal of Dhaka Medical College, 2015)
The aim of this study was to find out the outcome of cases requiring relaparotomy following caesarean delivery during the puerperium. This was a retrospective descriptive study set in a tertiary referral and teaching hospital i.e. Dhaka Medical College Hospital, Dhaka. Over a period of one year from January 1st to 31st December 2010, there were 5027 caesarean deliveries (53%-94%) out of a total of 9320 deliveries. Relaparotomy was done in 48 patients (0.95%) of the caesarean sections. The indications of repeat laparotomy were secondary postpartum haemorrhage (PPH) in 28 cases (58.33%), primary PPH due to uterine atony in 15 cases (31.3%), uterine sepsis with haemorrhage in 2 cases (4.17%), rectus sheath haemotoma in 2 cases (4.13%), internal haemorrhage after caesarean section in 1 case (2.08%). Of these 48 cases, in14 cases, primary caesarean section was done in this institution while 34 had caesarean delivery at other hospitals and clinics at (13 cases) and outside Dhaka (21 cases). Main surgeries performed at relaparotomy were subtotal hysterectomy in 29 cases, total hysterectomy in 9 cases, drainage of haematoma and peritoneal toileting in 4 cases, resuturing of uterine incisions in 5 cases, internal iliac arteries in 1 case. More than one procedure was often performed in one case. There were 6 maternal deaths following relaparotomy caused by shock following PPH, septicaemia and internal haemorrhage. Repeat laparotomy within six weeks of caesarean delivery was required 1 in 200 cases in this institute. Case fatality rate was (12.5%). Near miss fatalities were common. Majority on these were preventable. Identification of risk factors, adequate attention during primary surgery, expert decision, prompt intervention and proper case management during relaparotomy will improve the outcome. Centers carrying out caesarean section should have efficient blood transfusion service in the first place. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22693 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 41-47